СТИЛИСТИЧЕСКИЕ ФУНКЦИИ АВТОРСКОЙ РЕЧИ. (Eurasian Journal of Philology Science and Education, 2015)
This article deals with the expression forms of the authorspeech in the literary text, the samples from different texts aredescribed here.